2010
DOI: 10.1073/pnas.1005446107
|View full text |Cite
|
Sign up to set email alerts
|

Orientation saliency without visual cortex and target selection in archer fish

Abstract: Our visual attention is attracted by salient stimuli in our environment and affected by primitive features such as orientation, color, and motion. Perceptual saliency due to orientation contrast has been extensively demonstrated in behavioral experiments with humans and other primates and is believed to be facilitated by the functional organization of the primary visual cortex. In behavioral experiments with the archer fish, a proficient hunter with remarkable visual abilities, we found an orientation saliency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…In this sense, our research is similar to a recent study on archer fish, which have been shown to exhibit orientation-based saliency similar to humans (16). Unlike Mokeichev et al (16), however, who explored orientation-based saliency using a rapid forced choice procedure, our experiment was based on free-viewing visual search, reminiscent of the conditions under which this behavior is tested in humans. In both cases, bottom-up mechanisms are likely to play the main role in the observed behavior (although the effects of top-down influence, and of some implicit unspecified task, cannot be excluded), and in both cases the behavioral similarities in the reported findings suggest that visual processes, such as orientation-based visual search, may not necessarily require the elaborate cortical structures typically seen in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, our research is similar to a recent study on archer fish, which have been shown to exhibit orientation-based saliency similar to humans (16). Unlike Mokeichev et al (16), however, who explored orientation-based saliency using a rapid forced choice procedure, our experiment was based on free-viewing visual search, reminiscent of the conditions under which this behavior is tested in humans. In both cases, bottom-up mechanisms are likely to play the main role in the observed behavior (although the effects of top-down influence, and of some implicit unspecified task, cannot be excluded), and in both cases the behavioral similarities in the reported findings suggest that visual processes, such as orientation-based visual search, may not necessarily require the elaborate cortical structures typically seen in humans.…”
Section: Discussionmentioning
confidence: 99%
“…This is in stark contrast to the important ecological function of search strategies in all animals, which should have been optimized according to the ecological and survival needs of a species in the course of evolution. Notable exceptions are visual search strategies reported in pigeons (4,5) and recent orientation-saliency behavior found in archer fish (16).…”
mentioning
confidence: 99%
“…To address these questions we studied the archer fish [21][22][23][24][25][26] , a species that lacks a cortex 27 but exhibits complex visual behaviours and unique hunting practices. Owing to its remarkable ability to shoot down prey found on foliage above the water level, and its ability to learn to distinguish between artificial targets presented on a computer monitor in an experimental setting 28 , the archer fish exhibits overt target selection that can be leveraged for reporting psychophysical decisions in controlled lab experiments 24,26,29,30 .…”
mentioning
confidence: 99%
“…Owing to its remarkable ability to shoot down prey found on foliage above the water level, and its ability to learn to distinguish between artificial targets presented on a computer monitor in an experimental setting 28 , the archer fish exhibits overt target selection that can be leveraged for reporting psychophysical decisions in controlled lab experiments 24,26,29,30 . At the same time, electrophysiological recordings from the central nervous system of archer fish enable the necessary exploration of neural mechanisms underlying behavioural phenomena 31 .…”
mentioning
confidence: 99%
“…IN RECENT YEARS, THE ARCHER FISH has proved to be a very productive model in the study of many aspects of visual behavior, from retinal encoding (Tsvilling et al 2012;Vasserman et al 2010), eye movements (Ben-Simon et al 2009), animal competition (Schuster 2011), and visual acuity (Ben-Simon et al 2012a;Temple et al 2010Temple et al , 2013 to tracking of moving targets (Ben-Simon et al 2012b;Schlegel and Schuster 2008;Schuster et al 2006;Timmermans 2000Timmermans , 2001) and visual search (Mokeichev et al 2010). The productivity of the model can be explained, in part, by the ability of the archer fish to overtly report its visual decisions by employing a squirt of water from its mouth aimed at selected targets.…”
mentioning
confidence: 99%